Biological characteristics of gene expression features in pancreatic cancer cells induced by proton and X-ray irradiation. (1st May 2019) - Fujinaga, Haruo; Sakai, Yoshio; Yamashita, Tatsuya; Arai, Kuniaki; Terashima, Takeshi; Komura, Takuya; Seki, Akihiro; Kawaguchi, Kazunori; Nasti, Alessandro; Yoshida, Keiko; Wada, Takashi; Yamamoto, Kazutaka; et al.
Abstract: Background: Radiation therapy is an important alternative treatment for advanced cancer. The aim of the current study was to disclose distinct alterations of the biological characteristics of gene expression features in pancreatic cancer cells, MIAPaCa-2, following proton and X-ray irradiation. Materials and methods: Using cDNA microarray, we examined the gene expression alterations of MIAPaCa-2 cells following proton or X-ray irradiation. We also isolated the surviving MIAPaCa-2 cells after irradiation and analyzed their gene expression profiles. Results: Although the cytocidal effects of both types of irradiation were similar at sufficient doses in vitro and in vivo, the affected gene expression profile alterations of MIAPaCa-2 cells irradiated with protons were distinct from those irradiated with X-ray. Interestingly, clustering analysis of gene expression of the surviving MIAPaCa-2 cells was also completely discernible between the two types of irradiation. However, a similar cytocidal effect was still observed in the proton- and X-ray-irradiated surviving cells after re-irradiation, commonly showing biological effects related to apoptosis and cell cycle processes. Conclusions: Proton irradiation treatment for pancreatic cancer provides the distinct biological effect of steady gene expression alterations compared to X-ray irradiation; however, surviving cells from both types of irradiation were still susceptible to the cytocidal effects induced by proton re-irradiation treatment.